Persistent Changes in Hormones and Growth Factors Involved in Ageing in Patients That Recovered from Severe COVID-19 - Alice Cuchi-Cabral; André C. Palma; Guilherme A. Nogueira; Henrique Ceretta Oliveira; Suzimar F. Benato Fusco; Maria L. Moretti; Licio A. Velloso; Eliana P. Araujo (Diseases)
Background: The coronavirus disease-19 pandemic affected millions of people and its long-term impact on the health of survivors is under evaluation. Objectives: In this study, we hypothesized that severe coronavirus disease-19 could promote long-term changes in the blood levels of hormones and growth factors known to be involved in the regulation of ageing. Methods: We evaluated 49 patients that recovered from severe COVID-19 and compared them with matched controls that were never infected by the virus. The blood levels of growth hormone, insulin-like growth factor-1, insulin, brain-derived neurotrophic factor, nerve growth factor, oxytocin, ghrelin, platelet-derived growth factor, fibroblast growth factor-1, and transforming growth factor-beta were determined using enzyme-linked immunosorbent assays. Results: After six months of recovery, patients presented reduced blood levels of growth hormone, insulin-like growth factor-1, brain-derived neurotrophic factor, and platelet-derived growth factor. Fifteen months after, the reductions in the blood levels of all four hormones/growth factors persisted. Conclusions: Our study advances the field by identifying hormones and growth factors involved in ageing that undergo persistent changes in patients that recover from severe COVID-19. Further studies could explore the potential of the identified hormones/growth factors as therapeutic targets for the late complications and accelerated ageing that may affect patients recovering from severe COVID-19.